A Study of Geopolymer Fresh Properties and Mechanical Properties in 3D Concrete Printing - Noorhadi, Nur Fatin Nasuha; Abdullah, Siti Radziah (Recent Trends in Civil Engineering and Built Environment, 2021)
Due to its enormous potential to reduce wastage, labor needs, construction costs and expand design freelancing, 3D concrete printing has become broadly applied in the construction and building areas. This paper presents the general review of 3D printing by studying the material compositions by using fly ash and blast furnace slag, fresh properties and mechanical properties of geopolymer 3D printing. Some of the findings are fly ash and ground blast furnace slag need activators or replacement to increase the mechanical properties of the materials. The addition of activators brings greatly change to compressive strength, flexural strength, tensile strength and yield strength in curing 28 days. The use of fly ash speed up the buildability, flowability, extrudability and setting time of concrete mixtures. However, some areas such as the parameters of the flowability on using fly ash are rarely present by the researchers which is need more future investigations.